The Relationship between Fine Particle Matter (PM2.5) Exposure and Upper Respiratory Tract Diseases - Zaręba, Łukasz; Piszczatowska, Katarzyna; Dżaman, Karolina; Soroczynska, Karolina; Motamedi, Parham; Szczepański, Mirosław; Ludwig, Nils (Journal of personalized medicine, 2024)
PM2.5 is one of the most harmful components of airborne pollution and includes particles with diameters of less than 2.5 μm. Almost 90% of the world’s population lives in areas with poor air quality exceeding the norms established by the WHO. PM2.5 exposure affects various organs and systems of the human body including the upper respiratory tract which is one of the most prone to its adverse effects. PM2.5 can disrupt nasal epithelial cell metabolism, decrease the integrity of the epithelial barrier, affect mucociliary clearance, and alter the inflammatory process in the nasal mucosa. Those effects may increase the chance of developing upper respiratory tract diseases in areas with high PM2.5 pollution. PM2.5’s contribution to allergic rhinitis (AR) and rhinosinusitis was recently thoroughly investigated. Numerous studies demonstrated various mechanisms that occur when subjects with AR or rhinosinusitis are exposed to PM2.5. Various immunological changes and alterations in the nasal and sinonasal epithelia were reported. These changes may contribute to the observations that exposure to higher PM2.5 concentrations may increase AR and rhinosinusitis symptoms in patients and the number of clinical visits. Thus, studying novel strategies against PM2.5 has recently become the focus of researchers’ attention. In this review, we summarize the current knowledge on the effects of PM2.5 on healthy upper respiratory tract mucosa and PM2.5’s contribution to AR and rhinosinusitis. Finally, we summarize the current advances in developing strategies against PM2.5 particles’ effects on the upper respiratory tract.